Laser-treated microporous silicon-titanium dioxide photocatalyst for water treatment - Abdulbari, Hayder A.; Basheer, Esmail Abdullah Mohammed; Wafaa, Kamil Mahmood (2018)
Many materials have been implemented as photocatalyst and most recently the semiconductors. In top of the semiconductors materials, titanium dioxide which considered one of the most effective photocatalyst for water treatment application. Nevertheless, TiO2 application in water treatment still limited due to the low solar energy used by the system. These limitations are associated to the large band gap energy which limits the solar spectrum that activate the surface and most of the photoexcited electron-hole pairs tend to recombine in TiO2 surface, thus leading to a reduction in the photocatalytic performance. In this paper for the first time, Titanium dioxide was immobilized on laser-microporous silicon wafer type-p. The microporous silicon (MPSi) wafer was prepared by electrochemical etching assisted by laser projection.